Approaches for Genetic Discoveries in the Skin Commensal and Pathogenic Malassezia Yeasts - Ianiri, Giuseppe; Heitman, Joseph (Frontiers in Cellular and Infection Microbiology, 2020)
Malassezia includes yeasts belong to the subphylum Ustilaginomycotina within the Basidiomycota. Malassezia yeasts are commonly found as commensal on human and animal skin. Nevertheless, Malassezia species are also associated with several skin disorders, such as dandruff/seborrheic dermatitis, atopic eczema, pityriasis versicolor, and folliculitis. More recently, an association of Malassezia with Crohn’s disease, pancreatic ductal adenocarcinoma, and cystic fibrosis pulmonary exacerbation has been reported. To understand the genetic basis of Malassezia commensalism and pathogenicity, the availability of genomic and molecular tools plays a crucial role. In the present review we report genomics advances in Malassezia highlighting unique features that potentially impacted Malassezia biology and host adaptation. Furthermore, we describe the recently developed protocols for Agrobacterium tumefaciens-mediated transformation in Malassezia, and their applications for random insertional mutagenesis or targeted gene replacement strategies.